Chemical variation induced nanoscale spatial heterogeneity in metallic glasses. Issue 12 (2nd December 2018) - Wang, Neng; Ding, Jun; Luo, Peng; Liu, Yanhui; Li, Lin; Yan, Feng
ABSTRACT: Metallic glasses possess amorphous structures with inherent heterogeneity at the nanoscale. A combined experimental and modeling investigation to elucidate the chemical effect on such nanoscale heterogeneity in a Cu-Zr-Al metallic glass system is conducted. By using the dynamic atomic force microscopy, we reveal a reduction of the nanoscale spatial heterogeneity in the local viscoelastic response after introducing Al into the Cu50 Zr50 metallic glass. The change of such nanoscale heterogeneity can be contributed to the variation of local atomic structures. The addition of Al increases the population of the icosahedral short-range ordered clusters, thus reducing the structural heterogeneity at the nanoscale. GRAPHICAL ABSTRACT: IMPACT STATEMENT: This paper provides a combination between the nanoscale experimental and theoretical understanding of the chemical variation induced spatial heterogeneity in CuZrAl metallic glass and their impacts on the mechanical properties.